Comparison of various sol-gel derived metal oxide layers for inverted organic solar cells - Oh, Hyunchul; Krantz, Johannes; Litzov, Ivan; Stubhan, Tobias; Pinna, Luigi; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2011)
Inverted bulk-heterojunction solar cells have recently captured high interest due to their environmental stability as well as compatibility to mass production. This has been enabled by the development of solution processable n-type semiconductors, mainly TiO and ZnO. However, the device performance is strongly correlated to the electronic properties of the interfacial materials, and here specifically to their work function, surface states as well as conductivity and mobility. It is noteworthy to say that these properties are massively determined by the crystallinity and stoichiometry of the metal oxides. In this study, we investigated aluminum-doped zinc oxide (AZO) as charge selective extraction layer for inverted BHJ solar cells. Thin AZO films were characterized with respect to their structural, optical and electrical properties. The performance of organic solar cells with an AZO electron extraction layer (EEL) is compared to the performance of intrinsic ZnO or TiO EELs. We determined the transmittance, absorbance, conductivity and optical band gap of all these different metal oxides. Furthermore, we also built the correlations between doping level of AZO and device performance, and between annealing temperature of AZO and device performance. © 2011 Elsevier B.V.
Keywords: Al doped ZnO (AZO); Charge selective extraction layer; Inverted Organic Solar cells; Sol-Gel synthesis; TiOx; ZnO